Three-dimensional effects in laminar flow past a confined cylinder - V. M. Ribeiro (2012)
An experimental and numerical study on the Newtonian fluid flow around a confined cylinder placed in a rectangular duct was undertaken in order to assess three-dimensional effects on the flow patterns. The cylinder was placed at the mid-plane to define a symmetric geometry with a 50% blockage ratio (BR, ratio between the cylinder diameter and the thickness of rectangular section). The flow visualizations by streak photography and the velocity measurements by particle image velocimetry were carried out for three different aspect ratios (AR, ratio between the length and diameter of the cylinder) of 16,8 and 2 and the Reynolds number varied between creeping flow conditions (Re -> 0) up to the onset of time-dependent flow. The numerical calculations were performed in 3D meshes using an in-house finite volume code. They showed good agreement with experimental measurements and were also used to investigate the flow at very small and very large AR. For large values of AR, the results show unexpected velocity peaks near the cylinder end walls downstream of the cylinder for both inertia and diffusion controlled flow conditions. Increasing the aspect ratio of the cylinder does not reduce this local three-dimensional flow effect, which is found to occur near the ends of the cylinder at about one cylinder radius distance from the duct end walls. In contrast, reducing AR eliminated flow separation as expected for the Hele-Shaw type flows.